Can renalase be a novel candidate biomarker for distinguishing renal tumors? - Akkoc, R. F.; Aydin, S.; Goksu, M.; Ozcan Yildirim, S.; Eroksuz, Y.; Ogeturk, M.; Aydin, S. (Taylor & Francis Ltd, 2021)
Renalase (RNLS) is synthesized mainly in renal tissues. The function of RNLS in cancerous renal tissues has not been investigated. We investigated the synthesis of RNLS in chromophobe renal cell carcinoma, papillary renal cell carcinoma and clear cell renal cell carcinoma with Fuhrman grades (FG): FG1, nucleoli are absent or inconspicuous and basophilic; FG2, nucleoli are conspicuous and eosinophilic and visible but not prominent; FG3, nucleoli are conspicuous and eosinophilic; FG4, extreme nuclear pleomorphism, multinucleate giant cells, and/or rhabdoid and/or sarcomatoid differentiation. We used 90 tissue samples including 15 healthy controls, 15 chromophobe renal cell carcinoma tissues and 10 papillary renal cell carcinoma renal tissues: 12 FG1, 14 FG 2, 14 FG 3 and 10 FG4. RNLS in the tissue samples was measured using enzyme linked immunosorbent assay and immunostaining of RNLS in these tissues. RNLS was significantly greater in the chromophobe renal cell carcinoma and papillary renal cell carcinoma tissues than the control. The least amount of RNLS was found in the renal tissues of clear cell renal cell carcinoma FG1; the amount of RNLS increased as the FG grades increased. Because RNLS increased significantly in renal tissues due to cancer, except for clear cell renal cell carcinoma FG1, RNLS may be useful biomarker for distinguishing grades of renal cancer. Because RNLS increases cell survival, anti-RNLS preparations may be useful for treating cancer in the future.
Keywords: Biomarker; carcinoma; ELISA; fuhrman nuclear grade; human; renal tumors; renalase